Sistem Kontrol Teleskop Meade LX-600 Dengan Aplikasi Open Source - Adi Damanhuri (University of Muhammadiyah Sumatera Utara, 2019)
Now, astronomical observations including hilal observations are easier and simpler because of instruments equiped with computer-based technology. One of them is a telescope that is equipped by a automatical motor drive and computerized. Telescope control is now easier to do with applications based on open source operating systems, one of them is KStars application. With Meade LX-600 telescope owned by the departement of Ilmu Falak, Islamic Studies and Law Faculty UIN Sunan Ampel Surabaya, a control system was built using the KStars application based on open source, which has the advantage of no need to install additional drivers for connectivity with cables.